Rodzina w parafii Nowy Korczyn w drugiej połowie XVIII wieku na podstawie ksiąg metrykalnych (część 1) - Konrad Kołodziejczyk (Przeszłość Demograficzna Polski, 2016)
The article contains a demographicdescription of the ancient Polish familyexemplified with the parish of NowyKorczyn in the second half of the 18th century.The content of the article has beendetermined by the continuity and relativecompleteness of the records in the parishregisters on the one hand. On accountof the size of the parish registers (whichrequired a lot of time to investigate), thescope of research has been reduced tothe last 50 years of the First Republic. Asa result the source material comprises severalhundreds of reconstructed families;it has been used to analyse the basic problemsconcerning families of that time.The first part of the article presents a briefdescription of the parish of Nowy Korczyn,the aims, methods and sources. Themain part of the article contains a depictionof the reconstructed families (closed,complete and open), and an analysis of thetotal fertility rate. The final part of the articleconcentrates on the kind of fertilitytypical of the Nowy-Korczyn women (naturalor controlled), and is an attempt toanswer the question whether the womenused contraceptive methods.